The Effectiveness of Government Program Policies Through Sport Tourism (Triathlon) in Improving Regional Tourism Advancement in Bangka Regency - Rizaldi Rizaldi; Alfitri Alfitri; Waspodo Waspodo; Raniasa Putra (Green Publisher Indonesia, 2025)
This study analyzes the effectiveness of local government policy programs in developing sport tourism as a strategic approach to enhance regional tourism development in Bangka Regency. The research employed a descriptive qualitative approach using a case study method. Data were collected through in-depth interviews with key informants, observations, and documentation. The data analysis referred to the program effectiveness theory proposed by Kettner, Moroney, and Martin (2008), which includes five main indicators: effort, cost efficiency, results, cost-effectiveness, and impact. The findings indicate that the sport tourism program in Bangka Regency is considered effective. The local government demonstrated strong commitment through budget allocation, cross-sectoral collaboration, and the provision of supporting infrastructure for sporting events such as triathlons. From the perspectives of cost efficiency and cost-effectiveness, the program has produced optimal outcomes despite relatively limited funding. The program also succeeded in increasing tourist visits, empowering local MSMEs, and strengthening the region’s image as a sport tourism destination. The long-term impacts—such as the reinforcement of social networks, the growth of sports communities, and the improvement of regional tourism governance—further underline the program’s success. Nonetheless, there is still room for improvement, particularly in digital promotion, human resource capacity development, and measurable evaluation of economic impacts. Overall, sport tourism can serve as a strategic instrument for enhancing regional tourism competitiveness and supporting sustainable regional development.